A SYSTEM TO SUPPORT DECISION MAKINGS IN SELECTION OF AID RECEIVERS FOR CLASSROOM REHABILITATION FOR SENIOR HIGH SCHOOLS BY EDUCATION OFFICE OF PRINGSEWU DISTRICT BY USING SIMPLE ADDITIVE WEIGHING METHOD - Muhamad Muslihudin; Miswan Gumati (Bakti Nusantara Institute, 2017)
Pringsewu district as a new autonomous region has big potentials in education sector. Currently there are 12 public senior/vocational high schools and 27 private senior/vocational high schools under Education Office of Pringsewu district. There many schools still requiring attentions on school buildings, especially classrooms. To obtain classroom rehabilitation aids, a system to support decision making to determine which school has the right to receive aids from Education Office in Pringsewu district. In implementing system to support decision makings in selection of aid receivers for classroom rehabilitation in senior/vocational high schools by Education Office of Pringsewu district, there are five criteria to use; the physical condition of classroom, number of students, number of teachers and staffs, school income, and status of land ownership of the school. The problem in this research was to find best alternative based on predetermined criteria b using SAW (Simple Additive Weighing). The basic concept of SAW method is to find out weight rating of each alternative in an attribute, and then ranking process is conducted to determine best alternative.